Oxidative stress parameters in silver catfish (Rhamdia quelen) juveniles infected with Ichthyophthirius multifiliis and maintained at different levels of water pH - Garcia, L. O. (2011)
The aim of this study was to determine oxidative stress parameters in the liver, gill and muscle of silver catfish juveniles infected with Ichthyophthirius multifiliis and maintained at pH 5.0 or 7.0 for three days. Juveniles were infected by adding one I. multifiliis-infected juvenile and water containing theronts to tanks. After the appearance of white spots on the skin, infected juveniles exposed to pH 5.0 and 7.0 showed significantly higher thiobarbituric acid reactive substances (TBARS) levels in the liver and gills compared to uninfected juveniles. Liver of infected juveniles exposed to pH 7.0 showed higher catalase (CAT) and lower glutathione-S-transferase (GST) activities, but those maintained at pH 5.0 showed significantly higher GST activity than uninfected juveniles. The gills of infected juveniles showed significantly higher CAT (day two) and GST activity at both pH 5.0 and 7.0 compared to uninfected juveniles. Muscle of infected juveniles showed significantly lower CAT and GST activity and TBARS levels (at day three) when maintained at both pH 5.0 and 7.0 compared to uninfected juveniles. In conclusion, I. multifiliis infection induces liver and gill damage via lipid peroxidation products in silver catfish, but higher antioxidant enzyme activity could indicate a greater degree of protection against this parasite. © 2011 Elsevier B.V.